Performa Cacing Lumbricus rubellus terhadap Penambahan Tepung Cangkang Telur sebagai Media - N. C. Hartono; A. M. Fuah; V. A. Mendrofa; Winarno (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
Lumbricus rubellus is one of earthworm species that has been cultivated because its utility as feed for livestock and fish. The culture media for earthworms are mainly manure and compost. The purpose of this research was to observe the performance of Lumbricus rubellus given eggshell powder in different types and levels. This study used commercial eggshell flour and homemade eggshell flour with different levels (10%, 20%, 30%) mixed with cow dung as a medium. The results of the study showed that the addition of eggshell flour (commercial and homemade) as much as 10% showed a higher earthworm weight gain than other treatments but the cocoon production of the treatment was lower than the control (0% eggshell flour).